Tumor Necrosis Factor-Alpha Inhibitor Etanercept Does Not Alter Methotrexate-Induced Gastrointestinal Mucositis in Rats. Issue 2 (August 2017) - Kuiken, Nicoline S.S.; Rings, Edmond H.H.M.; Alffenaar, Jan-Willem C.; Havinga, Rick; Jurdzinski, Angelika; Groen, Albert K.; Tissing, Wim J.E.
ABSTRACT: Objectives: Gastrointestinal (GI) mucositis is a severe adverse effect of chemotherapy and radiotherapy. Proinflammatory cytokines are thought to play an important role in the pathophysiology of GI mucositis. We aimed to determine the effect of the tumor necrosis factor-alpha (TNF-α) inhibitor etanercept on the severity of mucositis in a previously established methotrexate (MTX)-induced GI mucositis rat model. Methods: Male Wistar rats received 60 mg/kg MTX on day 0 intravenously. Rats were treated daily with either etanercept (TNF-α inhibitor) 5 mg/kg or NaCl 0.9% subcutaneously from day −3 till day 3. Control rats received NaCl 0.9% intravenously and etanercept subcutaneously. The severity of mucositis was determined by intake, bodyweight, plasma citrulline, and by a function test (absorption of an oral glucose bolus). On day 4 and day 10 rats were terminated. Villus length, crypt length, intestinal myeloperoxidase, and plasma etanercept levels were determined. Results: The administration of MTX induced mucositis in all rats. Etanercept did not cause a change in the degree of mucositis. Bodyweight, intake, and glucose levels were not altered by etanercept; villus length was comparable; and there was no difference in myeloperoxidase and citrulline level. Etanercept levels in plasma were significantly increased in the etanercept rats ( P  < 0.05). Conclusions: TNF-α inhibitor etanercept did not alter the severity of mucositis in the rat, suggesting that targeting only the inflammatory pathway of TNF-α is not effective for decreasing the severity of GI mucositis induced by high-dose MTX. Etanercept alone is not useful for the treatment of MTX-induced GI mucositis. Abstract : Supplemental Digital Content is available in the text